2009
DOI: 10.1038/onc.2008.476
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Hypoxia-associated p38 mitogen-activated protein kinase-mediated androgen receptor activation and increased HIF-1α levels contribute to emergence of an aggressive phenotype in prostate cancer

Abstract: Androgen Receptor (AR) -signaling plays a critical role in the development and progression of prostate cancer. Tumor microvasculature contributes to continual exposure of prostate cancer cells to hypoxia-reoxygenation, however, the role of hypoxia-reoxygenation in prostate cancer progression and modulation of AR signaling is not understood. In the present study, we evaluated the effects of hypoxia-reoxygenation in LNCaP cells, a line of hormone responsive human prostate cancer cells. Our results demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 38 publications
0
73
0
Order By: Relevance
“…Previous studies have found that hypoxia activated AR only in the presence of androgen (Horii et al, 2007;Park et al, 2012). Others showed unliganded AR transactivation in cells exposed to hypoxia (Khandrika et al, 2009) or hypoxia only activated the AR at low androgen concentrations mimicking the castration-resistant stage (Mitani et al, 2011), involving AR, HIF-1a, and b-catenin forming a ternary complex on AREs (Mitani et al, 2012). Similarly, the effect of AR activation on HIF-mediated transcription was either induction (Mabjeesh et al, 2003;Horii et al, 2007) or no synergistic effect (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that hypoxia activated AR only in the presence of androgen (Horii et al, 2007;Park et al, 2012). Others showed unliganded AR transactivation in cells exposed to hypoxia (Khandrika et al, 2009) or hypoxia only activated the AR at low androgen concentrations mimicking the castration-resistant stage (Mitani et al, 2011), involving AR, HIF-1a, and b-catenin forming a ternary complex on AREs (Mitani et al, 2012). Similarly, the effect of AR activation on HIF-mediated transcription was either induction (Mabjeesh et al, 2003;Horii et al, 2007) or no synergistic effect (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1a accumulates to a high level in many solid tumors, including breast, prostate, colorectal, and pancreatic cancers (8)(9)(10) but is virtually undetectable in normal, well-oxygenated tissues (11)(12)(13). Cancer cells that contain high levels of HIF-1a are able to survive under extreme conditions, are resistant to therapy, and have a greater potential for metastasis (10,(14)(15)(16)(17)(18). Thus, the linking of HIF-1a levels to 5FU production could in theory attack the most aggressive tumors, while having limited or no effect on well-oxygenated, normal cells.…”
Section: Resultsmentioning
confidence: 99%
“…HIF-1a is a molecular signature of cancer cells that can survive under extreme conditions, are resistant to therapy, and have a greater potential for metastasis (14)(15)(16)(17)(18). A treatment method that could specifically target these cells could significantly improve the effectiveness of cancer treatments when used in combination with traditional therapies.…”
Section: Characterization Of Haps Proteins In Bacteriamentioning
confidence: 99%
“…Notably, VEGF is important in the regulation of normal and abnormal angiogenesis in the ovary (3,4,(13)(14)(15)(16)(17)(18), particularly in the newly formed corpus luteum (19)(20)(21)(22). Hypoxia is a potent stimulus for the expression of VEGF (14,23), as ovulation causes a decline of local oxygen concentration, producing a hypoxic environment, and may be the predominant stimulator for VEGF production in the developing corpus luteum (5,24).…”
Section: Introductionmentioning
confidence: 99%